The Principle of Prudence and Scope Limitation in the Discussion of the Indonesian Constitutional Court: Implications for Legal Reform and Judicial Decision Making - Fitria Esfandiari; Moh. Fadli; Hilaire Tegnan (Journal of Law and Legal Reform, 2025)
The principle of precaution is understood as a preventive action in facing uncertainty or potential risks, especially when the potential impact of an action could be harmful. The Constitutional Court, whose decisions are final and binding, also applies this principle in its decision-making process. This research analyzes the relationship between the precautionary principle and the Justice Deliberation Meeting (RPH). The research method used was normative legal research with a statutory, conceptual, and philosophical approach. The study results affirm that the characteristics of Constitutional Court justices, viewed from the theory of authority, are unique. The theory of authority in law refers to the power or authority an institution or legal body possesses to make legitimate and binding decisions. In the context of the Constitutional Court, its decisions have a distinctiveness that reflects this institution’s special nature and responsibility. Furthermore, the Constitutional Court’s final decisions are binding, prioritize public interest, and use comprehensive evaluations in testing laws, reflecting the application of the precautionary principle in maintaining the integrity of the Constitution and justice for the entire society. In the case of RPH, justices should also apply the precautionary principle by considering all aspects and potential impacts of the law on the Constitution and the sense of justice in society.